The Dual Regulation of Apoptosis by Flavivirus - Pan, Yuhong; Cheng, Anchun; Wang, Mingshu; Yin, Zhongqiong; Jia, Renyong (Frontiers in Microbiology, 2021)
Apoptosis is a form of programmed cell death, which maintains cellular homeostasis by eliminating pathogen-infected cells. It contains three signaling pathways: death receptor pathway, mitochondria-mediated pathway and endoplasmic reticulum pathway. Its importance in host defenses is highlighted by the observation that many viruses evade, hinder or destroy apoptosis, thereby weakening the host’s immune response. Flaviviruses such as Dengue virus, Japanese encephalitis virus and West Nile virus utilize various strategies to activate or inhibit cell apoptosis. This article reviews the research progress of apoptosis mechanism during flaviviruses infection, including flaviviruses proteins and subgenomic flaviviral RNA to regulate apoptosis by interacting with host proteins, as well as various signaling pathways involved in flaviviruses-induced apoptosis, which provides a scientific basis for understanding the pathogenesis of flaviviruses and helps in developing an effective antiviral therapy.